High-temperature pairing in a strongly interacting two-dimensional Fermi gas - Murthy, Puneet A.; Neidig, Mathias; Klemt, Ralf; Bayha, Luca; Enss, Tilman; Holten, Marvin; Zürn, Gerhard; Preiss, Philipp; Jochim, Selim (Science, 2018)
Tuning the atomic pairing Cold atomic gases are extremely flexible systems; the ability to tune interactions between fermionic atoms can, for example, cause the gas to undergo a crossover from weakly interacting fermions to weakly interacting bosons via a strongly interacting unitary regime. Murthy et al. studied this crossover in a gas of fermions confined to two dimensions. The formation of atomic pairs occurred at much higher temperatures in the unitary regime than previously thought. Science, this issue p. 452 The nature of the normal phase of strongly correlated fermionic systems is an outstanding question in quantum many-body physics. We used spatially resolved radio-frequency spectroscopy to measure pairing energy of fermions across a wide range of temperatures and interaction strengths in a two-dimensional gas of ultracold fermionic atoms. We observed many-body pairing at temperatures far above the critical temperature for superfluidity. In the strongly interacting regime, the pairing energy in the normal phase considerably exceeds the intrinsic two-body binding energy of the system and shows a clear dependence on local density. This implies that pairing in this regime is driven by many-body correlations, rather than two-body physics. Our findings show that pairing correlations in strongly interacting two-dimensional fermionic systems are remarkably robust against thermal fluctuations. Radio-frequency spectroscopy shows that strongly interacting fermions start pairing high above the critical temperature. Radio-frequency spectroscopy shows that strongly interacting fermions start pairing high above the critical temperature.